2015
DOI: 10.1039/c5em00247h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of exposure to organophosphate, carbamate, phenoxy acid, and chlorophenol pesticides in pregnant women from 10 Caribbean countries

Abstract: Pesticides are commonly used in tropical regions such as the Caribbean for both household and agricultural purposes. Of particular concern is exposure during pregnancy, as these compounds can cross the placental barrier and interfere with fetal development. The objective of this study was to evaluate exposure of pregnant women residing in 10 Caribbean countries to the following commonly used classes of pesticides in the Caribbean: organophosphates (OPs), carbamates, phenoxy acids, and chlorophenols. Out of 438… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…TCPy, DMTP, DEP, and DETP concentrations in our cohort were much lower than those reported for pregnant women from Shanghai (China) [14], Cincinnati (USA) [21], Mexico DF [35], and Canada [22, 24]. Similar concentrations of DEP and TCPy to those of our study were found in the Caribbean Islands [36] and Puerto Rico [23] studies, respectively, although the detection frequencies in our study were lower.…”
Section: Discussionsupporting
confidence: 76%
“…TCPy, DMTP, DEP, and DETP concentrations in our cohort were much lower than those reported for pregnant women from Shanghai (China) [14], Cincinnati (USA) [21], Mexico DF [35], and Canada [22, 24]. Similar concentrations of DEP and TCPy to those of our study were found in the Caribbean Islands [36] and Puerto Rico [23] studies, respectively, although the detection frequencies in our study were lower.…”
Section: Discussionsupporting
confidence: 76%
“…Epidemiological studies that investigated exposure to CA insecticides during development detected CAs or metabolites in 30% to 93% of samples from mothers/newborns of several countries (Barr and others 2010; Forde and others 2015; Ostrea and others 2009; Whyatt and others 2003) and in up to 11% of samples from children and adolescents (Needham and others 2005). While these and other studies found a significant exposure to CAs during development, we found few epidemiological studies describing developmental effects of this class of insecticide, and all of them focused on prenatal exposures (SM Table 6).…”
Section: Carbamates (Cas)mentioning
confidence: 99%
“…Insecticides with both similar and distinct modes of action are frequently used in the same crop (USDA 2014) and are concurrently identified in biological samples (e.g. (Barr and others 2010; Forde and others 2015; Reiler and others 2015). Despite that, there is still a restricted number of studies that investigate the effects and mechanisms associated with dual exposures.…”
Section: How To Improve Safetymentioning
confidence: 99%
“…However, since VOCs are ubiquitous in the environment and found in many common household products (Boyle et al, 2016), we assume that exposures to VOCs are just as likely to occur in Jamaica compared to other countries. Furthermore, pesticides are regularly used in the Wider Caribbean Region (Fernandez, Singh, & Jaffe, 2007) and studies have reported that pregnant women in Jamaica have higher urine concentrations of pesticides compared to other Caribbean countries (Forde et al, 2015), the U.S., and Canada (Dewailly et al, 2014). …”
Section: Introductionmentioning
confidence: 99%